Role-Playing Game as Learning Media To Support Online Learning - Satria, Vinza Hedi; Herumurti, Darlis (Universitas Pendidikan Ganesha, 2021)
Lack of learning media will affect the learning process in the classroom. Various learning media can motivate students in online learning activities. It causes learning media to be essential in the learning process. In the current era of online learning, students are prone to boredom and stress. Therefore this study aims to develop learning media with RPG (Role Playing Games). This research is exploratory because the field of play is vast, with validation using an E-GameFlow survey to assess the level of comfort of players when gaining knowledge. The research will be conducted on 15 junior high school students by distributing online questionnaires. The methods used to collect data are observation and questionnaires. The instrument used to collect data is a questionnaire. The technique used to analyze the data is descriptive qualitative and quantitative analysis. The results of each question on each aspect of E-GameFlow will be analyzed to find conclusions about the games that have been made. The results of the data obtained show that the lowest value is 5.49 in the challenge aspect, which is caused by a static game map and lack of guidance regarding the game. The overall results of E-GameFlow show that the game can provide comfort to players while providing learning materials. This is evident from no aspect with a score below the average.